Acute lower respiratory infections in Indigenous infants in Australia's Northern Territory across three eras of pneumococcal conjugate vaccine use (2006–15): a population-based cohort study. (June 2020) - Binks, Michael J; Beissbarth, Jemima; Oguoma, Victor M; Pizzutto, Susan J; Leach, Amanda J; Smith-Vaughan, Heidi C; McHugh, Lisa; Andrews, Ross M; Webby, Rosalind; Morris, Peter S; Chang, Anne B
Summary: Background: The burden of acute lower respiratory infection (ALRI) in Indigenous children of Australia's Northern Territory is among the highest globally. No published data exists on the effect of pneumococcal conjugate vaccine (PCV) introduction on ALRIs in this population beyond 2005. The aim of this study was to describe the rates of ALRI admissions to hospital in Indigenous infants in the Northern Territory from 2006 to 2015, across three periods of different PCV use. We hypothesised that broader valency PCVs would be more effective against hospitalisations for pneumonia. Methods: We did a retrospective population-based cohort study of Indigenous infants born in the Northern Territory followed up until age 12 months. Data were from administrative hospital and perinatal datasets. International classification of diseases codes (tenth revision, Australian modification; ICD-10AM) were used to identify respiratory hospitalisations of interest: all-cause ALRI, all-cause pneumonia, bacterial pneumonia, viral pneumonia, influenza-like illness (ILI), respiratory syncytial virus ALRI (RSV-ALRI), and pneumococcal ALRI. Incidence rates were compared between PCV eras (7-valent PCV [PCV7], 2006–09; 10-valent PCV [PCV10], 2009–11; and 13-valent PCV [PCV13], 2011–15) using interrupted time trend analysis and negative binomial regression. Findings: For children born between Jan 1, 2006, and Dec 31, 2015, 4138 ALRI episodes (31% of all hospitalisations) occurred among 2888 (20%) of the 14 594 infants. The overall ALRI hospitalisation rate was 29·7 episodes per 100 child-years. Prominent risk factors associated with ALRI hospitalisation were living in a remote community or the Central desert region, being born preterm or with low birthweight. ALRI rates were lowest in the PCV13 era, in association with a significant reduction in bacterial pneumonia hospitalisations in the PCV13 era compared with the PCV10 (incidence rate ratio 0·68, 95% CI 0·57–0·81) and PCV7 (0·70, 0·60–0·81) eras. In contrast, RSV-ALRI rates were 4·9 episodes per 100 child-years in each era. Interpretation: A 30% reduction in bacterial-coded pneumonia hospitalisations in the Northern Territory during the era of PCV13 immunisation supports its ongoing use in the region. Despite the reduction, one in five Indigenous infants born in the region continue to be hospitalised with an ALRI in their first year of life. Future gains require multifaceted environmental and biomedical approaches. Funding: National Health and Medical Research Council of Australia.